2022
DOI: 10.1029/2022gl098082
|View full text |Cite
|
Sign up to set email alerts
|

From Microorganisms to Biosignatures: Subcritical Water Extraction as a Sample Preparation Technique for Future Life Detection Missions

Abstract: The discovery of potentially habitable conditions on Europa and Enceladus has led to an increased interest in searching for extant life in these locations (Chyba & Phillips, 2002;Porco et al., 2017). There is a consensus that multiple lines of evidence will be required to provide the extraordinary proof required to support any claims of the detection of extraterrestrial life (Hand et al., 2017). Among the possible lines of evidence, chemical biosignatures are considered key because of the way that life is expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The high temperature and pressure conditions used in subcritical water extraction leads to cell lysis and hydrolysis of macromolecules into its building blocks. We have recently demonstrated the use of SCWE for the release of amino acids from microorganisms . Here, we demonstrate that SCWE also releases fatty acids by hydrolysis of lipids.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The high temperature and pressure conditions used in subcritical water extraction leads to cell lysis and hydrolysis of macromolecules into its building blocks. We have recently demonstrated the use of SCWE for the release of amino acids from microorganisms . Here, we demonstrate that SCWE also releases fatty acids by hydrolysis of lipids.…”
Section: Resultsmentioning
confidence: 65%
“…We have recently demonstrated the use of SCWE for the release of amino acids from microorganisms. 28 Here, we demonstrate that SCWE also releases fatty acids by hydrolysis of lipids. Because of the low solubility of fatty acids in water, a precipitate is formed after SCWE.…”
mentioning
confidence: 56%
“…18 Our work showed that moderate acidification of the sample with 10 mM HCl results in higher extraction/hydrolysis yields without a negative impact on the subsequent measurement of amino acid biosignatures. 15,18 To date, though, no work has explored the effect of SCWE on amino acid distributions when performed under alkaline conditions. The effect of alkaline conditions is important because models based on data observed by the Cassini spacecraft suggest that Enceladus' ocean is a Na−Cl−CO 3 buffer with an alkaline pH of ∼8−12.…”
Section: Introductionmentioning
confidence: 70%
“…It is noteworthy that the recoveries of most amino acids did improve with higher temperature and longer extraction times; however, some amino acids, such as aspartic acid and glycine, degraded. SCWE is also suitable for lysing cells and spores, while simultaneously hydrolyzing proteins that can subsequently be analyzed by, for example, CE (Cieslarova et al, 2022). Urey, an instrument based on SCWE and microchip electrophoresis (Mars Organic Analyzer, MOA, see Section 5.1), was initially under development for the Rosalind Franklin rover; however, it was descoped before the first prototype was manufactured (Amashukeli et al, 2008;Aubrey et al, 2008;Bada et al, 2008).…”
Section: Subcritical Water Extractionmentioning
confidence: 99%